Dr. Edwin Wright Letters: Wilfred R. Flack - (Author); (Interviewer); (Publisher) (2011)
Notes - Mr. William Flack's family arrived in Athabasca Landing around 1887. Mr. Flack writes about life in Athabasca and the district around 1911. He talks of businesses, families, and occupations. Mr. Flack also mentions several amusing anecdotes that involved family and friends (2 pages)